3D Functional Microgels: Modular and Customized Fabrication of 3D Functional Microgels for Bottom‐Up Tissue Engineering and Drug Screening (Adv. Mater. Technol. 5/2020). Issue 5 (11th May 2020) - Yang, Wenguang; Cai, Shuxiang; Chen, Yibao; Liang, Wenfeng; Lai, Youbin; Yu, Haibo; Wang, Yuechao; Liu, Lianqing
Abstract : In article number 1900847, Wenguang Yang, Haibo Yu, Lianqing Liu, and co‐workers demonstrate an optofluidic maskless lithography system that combines digital micromirror device (DMD)‐based 3D printing and microfluidic technologies for fabricating 3D functional microgels. With this system, 3D microgels can be custom designed online and manufactured modularly in a microfluidic device. Furthermore, cells in microgels exhibit features that are more similar to the complex in vivo conditions, including morphology, proliferation, and drug resistance.